RISYWAH DALAM RANGKA MENGAMBIL HAK - Syafiq Riza Hasan; Teguh Dwi Cahyadi; Farchan Mu'aziz (Al-Majaalis : Jurnal Dirasat Islamiyah, 2023)
ABSTRACT The practice of bribery is not new in society. Bribes have become an alternate pathway to those who want to make their business whether in the public or private services sector. According to the 2020 GCB survey in Indonesia, 30% of the public claim to have paid bribes in the last year when accessing public services. In Islam, the practice of bribery is clearly forbidden by Allah and His Messenger. On the other hand, there are conditions where some agencies in public and private services are forcing a person to bribe because of the prevailing system. If someone does not bribe, then his rights will not be given or slowed down. From this study, the researchers want to know the legal status of bribing in order to take rights. This research uses a qualitative approach with literature study techniques in collecting data and analyzing it with a descriptive method. The result of this study is that bribery given in conditions of taking rights or avoiding injustice is permissible with several conditions. Keywords: rights; take rights; bribery